Фізіологічний профіль тхеквондистів високого класу - Михалюк, Євген Леонідович; Сиволап, Віталій Вікторович; Ткаліч, Ігор Вячеславович (My University, 2011)
В статье изучено влияние спортивной квалификации и пола на показатели вариабельности сердечного ритма, центральной гемодинамики и физической работоспособности у спортсменов высокого класса, занимающихся тхеквондо. Основное отличие тхеквондистов уровня МС-МСМК по сравнению со спортсменами квалификации 1 разряд-КМС заключается в преобладании парасимпатического звена ВНС, меньших величинах ЧСС, СИ (преобладание гипокинетического типа кровообращения) у мужчин, а у тхеквондисток, кроме того, в больших величинах PWC170/кг и ИФС. Гендерные различия тхеквондистов уровня МС-МСМК демонстрируют усиление симпатического звена ВНС у мужчин и отсутствие достоверных различий среди показателей PWC170/кг и ИФС. The influence of gender and level of sporting qualification on heart rate variability (HRV), central hemodynamics and physical working capacity of high-class taekwondo athletes was examined in this article. The main difference of taekwondo athletes – Master of Sports and Master of Sports of International grades in comparison with athletes of the first grade Candidate in masters of sport consists in prevailing of parasympathetic branch of vegetative nervous system (VNS), less values of heart rate, CI (prevalence of hypokinetic type of blood circulation) in males and larger values of PWC170/кg and FSI in female taekwondo athletes. The gender differences of taekwondo athletes – Master of Sports and Master of Sports of International grades demonstrate the reinforcement of sympathetic branch of VNS in male athletes and absence of reliable distinctions of PWC170/кg and FSI values.
Keywords: тхеквондо; чоловіки; жінки; варіабельність серцевого ритму; центральна гемодинаміка; фізична працездатність; індекс функціонального стану; taekwondo; males; females; heart rate variability; central hemodynamics; physical working capacity; functional state index